Diagnosis and Management of Barrett's Esophagus: A Retrospective Study Comparing the Endoscopic Assessment of Early Esophageal Lesions in the Community versus a Specialized Center. (29th March 2016) - Rayner-Hartley, Erin; Takach, Oliver; Galorport, Cherry; Enns, Robert A.
Abstract : Specialized endoscopic evaluation for patients with Barrett's esophagus (BE) is well supported; however, no studies have shown that centers with expertise provide better quality care for BE with high-grade dysplasia or early adenocarcinoma. In this study, the investigators aimed to evaluate the management and clinical course for patients treated in a community practice versus a specialized BE center. Methods . A retrospective analysis of referrals from the community to our specialized center for evaluation of BE at St Paul's Hospital Division of Gastroenterology between January 2007 and February 2014 was performed. Subjects were patients who were referred for BE and dysplasia and subsequently reevaluated by endoscopy. The pathology and endoscopy reports from the community and our center were reviewed. Inclusion criteria were as follows: being ≥ 19 years old and pathologic diagnosis of BE or dysplasia in the community. Exclusion criteria were as follows: incomplete pathology data or incomplete endoscopy reports from the community physicians. Results . A total of 77 patients were reviewed. The staging of 28.9% of patients referred from the community was changed from the initial pathological diagnosis. 18.4% of these patients were upstaged. Using Fischer's exact test, we showed that, in our specialized center, endoscopic impressions correlated significantly with pathology results (p < 0.0001 ).